Perosnal Branding through social media: The role of personal branding on professional growth, networking, and career development - Jegashini, K.; Sathana, V. (University of Jaffna, 2024)
Purpose: This study explores how individuals utilize social media to establish personal brands, focusing on their impact on professional growth, networking, and career development, offering valuable insights into this evolving field. Design/Methodology/Approach: This study used a quantitative approach, surveying final year students and graduates from University of Colombo and University of Jaffna using convenient sampling and online questionnaires. Regression analysis was used to investigate the impact of social media usage on personal branding, specifically its influence on professional growth, networking, and career development. Findings: The result reveals that social media is essential for personal branding, career development, networking, and professional growth, bridging the gap between personal and professional spheres. A strong online personal brand attracts potential employers, peers, and business leaders for collaboration, highlighting its significant impact on professional success and personal fulfillment. It is crucial in today's job market, promoting continuous growth, networking, and career advancement through digital identities for individuals and organizations. Research limitations: This study only looked at branding on social media from the standpoint of individuals. It’s limited to the Colombo and Jaffna university final year students and graduates. Implications: Those who use social media for personal branding effectively can have a big impact on their career path, highlighting its visibility, potential for knowledge demonstration, network growth, and career advancement. It suggests that this knowledge can be applied to organizational social media policies, aligning with employees' preferred platforms. Integrating this research into educational curricula can equip students and professionals with the necessary skills for effective social media use.
Keywords: Personal branding; Social media; Professional growth; Networking; Career development